Pancasila sebagai landasan etika dalam mengatasi tantangan cyberbullying: Menumbuhkan empati pada generasi Z - Adawiyah, Rabi’ Atul; Qoimuddin, Qoimuddin; Nasywa, Nadise Putri Raina Anya Ariella (Maliki Interdisciplinary Journal, 2024)
Cyberbullying occurs when someone bullies a victim via the internet or social media so that they cannot defend themselves easily. It can also be intended for a group of people who treat someone in an unpleasant way by sending messages, texts, photos, images or videos to someone’s social media account with the aim of insulting, insulting, harassing or discriminating against someone. This research uses conceptual analysis as an approach. The aim of this research is to identify the characteristics of people who commit cyberbullying, the factors that encourage cyberbullying, and the punishments imposed on those who do it. The results of our discussion show that the reason teenagers commit cyberbullying is their dislike of other people by insinuating them with harsh negative sentences with the aim of entertaining social media users, causing feelings of hatred, and making them feel like they are better and better than other people. other. The focus of this research is to increase awareness among teenagers, both pupils and students, about the importance of using social media wisely and carefully to avoid becoming the next victim of cyberbullying